SWEAR WORDS IN GITLOST’S TWITTER ACCOUNT: KINDS AND FUNCTION - Hapsari, Nunuk Tri; Pramana, Clarhyta Cahya (Sekolah Tinggi Bahasa Asing LIA Yogyakarta, 2023)
Language and social interaction are in accordance with the existing norms in society. By paying attention to these norms, we are expected to also pay attention to the choice of words that will be used in communication. In informal situations, swearing words are often used to respond to conversations on many social networks. One of them is Twitter. The phenomenon of using swearing words is found on the Twitter account called @gitlost or Developers Swearing. The research attempts to identify and describe the type and function of swear words used in that account. In collecting data, swear words were collected by observing all tweets according to a predetermined time span, then classified to find out the types of swear words and the function of swear words used based on the theory of Ronald Wardhaugh and Lars‐Gubbar Andersson and Richard Hirsch. The results of this study indicate that swear words are used to express feelings. Swear words are not only used to express anger but also happiness. This research shows that swear words are used based on their functions as expletive, abusive, humoristic, and chronic.